2022
DOI: 10.3390/antiox11112290
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Oxidative Ecology along an Aridity Gradient in a Mammalian Subterranean Species

Abstract: Climate change has caused aridification which can alter habitat vegetation, soil and precipitation profiles potentially affecting resident species. Vegetation and soil profiles are important for subterranean mole-rats as increasing aridity causes soils to become harder and geophytes less evenly distributed, and the inter-geophyte distance increases. Mole-rats obtain all water and dietary requirements from geophytes, and thus digging in harder soils may amplify stressors (hyperthermia, dehydration- or exercise-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 147 publications
1
9
0
Order By: Relevance
“…The roles of the kidney include water regulation and filtration, and detoxification of substances absorbed by the digestive system (Brzoska et al., 2003 ). Greater kidney mass could indicate links to physiological responses to heat and dehydration such as increased water regulation and water turnover, as well as a greater ability for water retention which can be utilised during periods of stress, starvation, and dehydration (Jacobs et al., 2020 , 2022 ). Other rodent and mole‐rat studies have explored the differences in kidney mass, size, function, and metabolism in arid and mesic regions, with similar findings (Al‐Kahtani et al., 2004 ; Jackson et al., 2004 ; Jacobs et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The roles of the kidney include water regulation and filtration, and detoxification of substances absorbed by the digestive system (Brzoska et al., 2003 ). Greater kidney mass could indicate links to physiological responses to heat and dehydration such as increased water regulation and water turnover, as well as a greater ability for water retention which can be utilised during periods of stress, starvation, and dehydration (Jacobs et al., 2020 , 2022 ). Other rodent and mole‐rat studies have explored the differences in kidney mass, size, function, and metabolism in arid and mesic regions, with similar findings (Al‐Kahtani et al., 2004 ; Jackson et al., 2004 ; Jacobs et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greater kidney mass could indicate links to physiological responses to heat and dehydration such as increased water regulation and water turnover, as well as a greater ability for water retention which can be utilised during periods of stress, starvation, and dehydration (Jacobs et al., 2020 , 2022 ). Other rodent and mole‐rat studies have explored the differences in kidney mass, size, function, and metabolism in arid and mesic regions, with similar findings (Al‐Kahtani et al., 2004 ; Jackson et al., 2004 ; Jacobs et al., 2022 ). Many bulbs found in the Northern Cape, where the arid populations in this study occur, have been found to be toxic, such as the bulbs of the Drimia plants (Manganyi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobs et al [ 5 ] investigated the impact of aridification on wild common mole rats and their oxidative status along an aridity gradient. Liver oxidative status showed no significant change with aridity levels.…”
mentioning
confidence: 99%